Invasive Alien Species - Threat to Biodiversity and Economy of the Country - Goyal, A. K. (Indian Forester, 2005)
Invasive Alien Species (lAS) cause damages amounhng to billions of dollars throughout the. world across a wide range of sectors including agriculture, forestry, fisheries, human health and tourism, threatening ecdnomic growth, prosperity as well as the environment. During the last one decade, there has been a lot of awakening to deal with lAS effectively which needs cooperation and coordination among countries as well as various agencies within countries. A number of international and regional institutions have been established for co-ordination and co-operation among the countries. A few countries have passed separate legislation to manage lAS and some others are in the process of doing so. The Forest Invasive Species (FIS) are of direct relevance to the forestry sector. In India, we need to create awareness among the people and various agencies about the harmful effects of FIS on the economy of the country and have appropriate coordination mechanisms to effectively deal with FIS. There is need to re-orient research priorities for finding out various cost effective methods to control and manage the existing FIS.